Molecular characterization of dengue virus 1 from autochthonous dengue fever cases in Croatia. (22nd December 2012) - Kurolt, I. C.; Betica‐Radić, L.; Đaković‐Rode, O.; Franco, L.; Zelená, H.; Tenorio, A.; Markotić, A.; Gould, E.
Abstract In the summer of 2010, two autochthonous dengue fever cases were detected in Croatia. Here we report the retrospective detection of an additional case of dengue fever, representing the first sustained autochthonous transmission in Europe since 1928. In addition, we present the phylogenetic analyses based on two sequences from the Pelješac peninsula, southern Croatia. The sequences were identified as dengue virus genotype 1 and recovered from two out of the three Pelješac patients in whom infection occurred.